THE APPLICATION OF LITERACY CULTURE IN GROWING READING INTEREST IN SMP NEGERI HINDU 3 BLAHBATUH GIANYAR: A CASE STUDY - Putu Agus Manik Wira Pratama; Ni Wayan Swarniti (Widyasrama, 2021)
Literacy is a person's ability to develop potential and skills in processing and understanding information while doing reading and writing activities. The purpose of this research Making junior high schools as a means of application a literacy culture so that students can manage knowledge through the best possible application of literacy. This research was designed as qualitative research. The research used to collect data is observation, interview and documentation. The results of the reseacrh (1) the school's strategy in application of literacy culture to growing reading interest in SMP Negeri Hindu 3 Blahbatuh Gianyar, namely library room facilities, borrowing books, giving book prizes to achievers student, making wall magazine, library schedules and reading corner. (2) the obstacles faced by schools in the application of literacy culture in growing reading interest in SMP Negeri Hindu 3 Blahbatuh Gianyar there are three, namely not all teachers have a good literacy culture, different student abilities, and the lack of parents role in making habit of reading books at home (3) school efforts in overcoming obstacles to the application of literacy culture at SMP Negeri Hindu 3 Blahbatuh Gianyar, namely using variation learning methods, procurement of books and providing an attractive literacy environment in school.